Analysis of Village Infrastructure Project Success Factors by Considering Implementation Risks - Yudha Adi Kusuma; Siti Muhimatul Khoiroh (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2023)
Rural areas play an important role in supporting the circulation of a people-based economy through equitable development. One form of development that villages need is infrastructure. Difficult access to infrastructure causes villagers to urbanize in the city. This condition was also experienced by ABC Village before the Nawa Cita program, which made the flow of infrastructure development run massively. The infrastructure development process requires support and cooperation between the village government and the village community. This research examines the impact of infrastructure development and its risks. The results of the study of village government policies and the role of the community have a positive effect on the success of infrastructure projects. Model measurement with the SEM method is fit. The results of the risk analysis showed that there were 5 high-category risks, 12 medium-category risks, and 14 low-category risks. Kawasan desa memegang peranan penting dalam mendukung perputaran ekonomi berbasis kerakyatan melalui pemerataan pembangunan. Salah satu bentuk pembangunan yang dibutuhkan desa adalah aspek infrastruktur. Sulitnya akses infrastruktur menyebabkan warga desa melakukan urbanisasi ke kota. Kondisi ini juga dialami oleh Desa ABC sebelum adanya program Nawa Cita yang membuat arus pembangunan infrastruktur berjalan masif. Proses pembangunan infrastruktur membutuhkan dukungan dan kerja sama antara pemerintah desa dengan masyarakat desa. Penelitian ini mengkaji terhadap dampak pembangunan infrastruktur dan risikonya. Hasil kajian terhadap kebijakan pemerintah desa dan peran masyarakat berpengaruh positif terhadap keberhasilan proyek infrastruktur. Pengukuran model dengan metode SEM bernilai fit. Hasil analisis risiko diketahui bahwa terdapat 5 risiko kategori tinggi, 12 risiko kategori sedang dan 14 risiko kategori rendah.